Sustainable Company Development in a Systemic Perspective (American Journal of Management, 2022)
After a short outline of the systemic approach in management and corporate governance with the most important topic-relevant concepts of this approach, the current and future socio-ecological challenges for companies in this systemic context will be explained. In addition to general examples of these systemic aspects and concrete possibilities for action, the challenges in this context are briefly discussed using the automotive industry as an example.After some examples of typical systemic aspects in this context, an explanation of the general three strategy options efficiency, consistency and sufficiency follows, including examples, as well as notes on their manifold systemic interdependencies with each other, e.g. systemic rebound effects.Finally, the approach of biocybernetics is presented in a short overview as a special methodological support for a system-oriented analysis and qualified action orientation in this topic area.
Keywords: management; systemic approach; interconnected thinking; sustainability strategies; path dependency; systemic rebound effects